25-HYDROXYVITAMIN D (25-OHD) LEVELS in TURKISH GERIATRIC POPULATION: A NATIONWIDE STUDY: 25-OHD LEVELS in TURKISH GERIATRIC POPULATION - Caglayan, Murat (Journal of Medical Biochemistry, 2022)
Background: 25-hydroxyvitamin D (25-OHD) deficiency is a major health problem worldwide and is associated with many chronic diseases in geriatric population. There is not any 25-OHD levels data among individuals overage 65 so far in Turkey. The aim of this study is to assess 25-OHD levels and the seasonal variations in people over the age of 65 living in Turkey. Methods: Working across Turkey, 2016, and 2017, the number of tests studied vitamin D in the population over the age of 65 in 2018 were included. Age, gender and seasonal average values were defined. The study data were obtained from the database of the Ministry of Health. Kolmogorov-Smirnov test was used for the distribution of the data. Median and interquartile range (IQR) were calculated for all categories, as the data were non-parametric. Results: The number of tests belonging to geriatric individuals included in the study was 305,329 tests for 2016, 576,452 tests for 2017 and 752,837 tests for 2018. The median and the IQR of the 25-OHD in elderly population were 16 ng/mL (IQR 7.45-24.55 ng/mL), 16.1 ng/mL (IQR 7.8-24.4 ng/mL), 16.4 ng/mL (IQR 8.95-23.85 ng/mL) respectively. Conclusions: In Turkey during the period of seasonal sunlight, although it is in 25-OHD levels in older men tend to increase this variability was observed in elderly women. This suggests that older women tend to live more sedentary and do not get enough of the sunrays. The median 25-OHD levels of individuals over the age of 65 tend to decrease each year.